2020
DOI: 10.1007/s12144-020-00898-8
|View full text |Cite
|
Sign up to set email alerts
|

The strengthening starts at home: Parent–child relationships, psychological capital, and academic performance – a longitudinal mediation analysis

Abstract: This longitudinal study examines how academic psychological capital mediates between parent child relationships and academic performance in a group of high school students. The sample consisted of 402 students (217 girls and 187 boys) aged between 14 and 17 years. Using a three wave design, as hypothesized, a significant indirect effect was found between (good) parent child relationships (assessed at time 1) and academic performance (assessed at time 3) via academic PsyCap (assessed at time 2). Students who pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 59 publications
3
28
0
Order By: Relevance
“…This study found that psychological capital played a mediating role in the relationship between family intimacy and relapse tendency. This is consistent with previous studies [72]. Good communication and strong emotional Table 7 The mediating effect of psychological capital on different levels of self-efficacy ties among family members are predictors of the development of positive qualities such as optimism and selfefficacy [29], whereas family conflict and low levels of family intimacy predispose individuals to problems such as pessimism and difficulties with social adjustment [73] and a lack of good coping strategies.…”
Section: Analysis Of the Mediating Role Of Psychological Capital In The Relationship Between Family Intimacy And Relapse Tendencysupporting
confidence: 89%
See 1 more Smart Citation
“…This study found that psychological capital played a mediating role in the relationship between family intimacy and relapse tendency. This is consistent with previous studies [72]. Good communication and strong emotional Table 7 The mediating effect of psychological capital on different levels of self-efficacy ties among family members are predictors of the development of positive qualities such as optimism and selfefficacy [29], whereas family conflict and low levels of family intimacy predispose individuals to problems such as pessimism and difficulties with social adjustment [73] and a lack of good coping strategies.…”
Section: Analysis Of the Mediating Role Of Psychological Capital In The Relationship Between Family Intimacy And Relapse Tendencysupporting
confidence: 89%
“…Thus, even when recovering PWUD feel the same level of family emotional connection, differences in psychological capital can influence hope and optimism about future lives, PWUD's belief that they can quit drugs, and their ability to make behavioural choices related to substance abuse. However, it has also been shown that levels of psychological capital are influenced by family [72]. PWUD who perceive good family emotional connections have higher self-confidence and positive optimism and possess the determination and hope to rebuild their lives and reform, and receiving emotional support from family enables individuals to recover quickly from difficult situations and reduce use of drugs to de-stress.…”
Section: Analysis Of the Mediating Role Of Psychological Capital In The Relationship Between Family Intimacy And Relapse Tendencymentioning
confidence: 99%
“…Academic research performance is one of the most relevant outcomes in the university setting [18]. It refers to the behaviors and achievements that students have acquired in a university program.…”
Section: Academic Research Performancementioning
confidence: 99%
“…Psychological capital is an intrinsic and stable psychological trait exhibited during individuals' growth and development [41]. It is considered to be a state-like positive psychological construct that is highly involved in task performance and reaching goals [18]. As a collection of core qualities and capabilities, the competence has an effect on psychological capital.…”
Section: The Mediating Role Of Psychological Capitalmentioning
confidence: 99%
See 1 more Smart Citation